2020
DOI: 10.21203/rs.3.rs-114499/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential kinetics of T cell and antibody responses delineate dominant T cell epitopes in long-term immunity after COVID-19

Abstract: Long-term immunity to SARS-CoV-2 is crucial for the development of herd immunity and the aim of vaccination approaches. Reports on rapidly decreasing antibody titers question the efficacy of humoral immunity. The relevance of T cell memory after COVID-19 is yet unclear. Longitudinal analysis of SARS-CoV-2 immunity in convalescents up to six months post-infection revealed decreasing and stable spike and nucleocapsid antibody responses, respectively. In contrast, T cell responses remained robust and even increas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Key characteristics of the control group populations are summarized in Table S6. Samples from human COVID-19 convalescent individuals (HCs) for analyses of T cell responses to specific and cross-reactive SARS-CoV-2 epitope compositions (EC) and samples for analyses of T cell responses after mRNA-based vaccines were previously described (9,14,18,41).…”
Section: Control Sample Cohortsmentioning
confidence: 99%
See 2 more Smart Citations
“…Key characteristics of the control group populations are summarized in Table S6. Samples from human COVID-19 convalescent individuals (HCs) for analyses of T cell responses to specific and cross-reactive SARS-CoV-2 epitope compositions (EC) and samples for analyses of T cell responses after mRNA-based vaccines were previously described (9,14,18,41).…”
Section: Control Sample Cohortsmentioning
confidence: 99%
“…Although it is undisputed that neutralizing antibodies induced by COVID-19 vaccines provide the first line of antiviral defense (5,6), spike-specific antibody titers tend to wane quickly and show limited neutralizing activity against newly arising variants of concern (VOCs) (7). In contrast, T cells were shown to mediate long-term immunity that is largely conserved against VOCs after SARS-CoV-2 infection and vaccination (5,8,9). T cell immunity is of central importance for patients unable to mount humoral immune responses, comprising individuals with congenital B-cell deficiency, but also cancer patients with disease or treatment related B-cell depletion that are at high risk for a severe course of COVID-19 (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even COVID-19 infection demonstrated that T cell response is important to generate memory response and lower severity in infected patients (14,15,16,17). Other studies concluded that nucleocapsid protein has to be included in further vaccine strategy (18,19,20,21). This can be a promising strategy to curb circulating Delta (22), Omicron variants (23) and hybrids (24) simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no data are available on SARS-CoV-2-directed T cell responses in cancer patients. In the meantime, multiple studies have identi ed the central role of SARS-CoV-2-speci c T cell responses for the clinical course of COVID-19 as well as for the development of long-term immunity (18)(19)(20)(21)(22)(23)(24)(25). This comprises evidence for potential pre-existing immunity mediated by T cells cross-reactive to human common cold coronaviruses (HCoV), which may provide a certain degree of protection against severe illness upon COVID-19 (18,19,21).…”
Section: Introductionmentioning
confidence: 99%